Emergency Nurse Retention: Understanding Success Factors for the Retention of Emergency Department Nurses Employed by a New Zealand District Health Board - Kistan, Leslie (Auckland University of Technology, 2025)
Nursing retention is a growing concern for the health workforce, especially in high-acuity and pressurised areas, such as emergency departments (EDs). For the emergency nurse workforce, there is pressure from higher patient: nurse ratios, staff shortages, and complex, acutely presenting co-morbidities. The New Zealand (NZ) media have been regularly reporting overcrowding, escalating presentations, long waits, incidents of violence, and, most concerningly, preventable patient deaths within EDs. The recent COVID-19 pandemic has exacerbated these issues. This research aimed to examine the key factors contributing to successful retention of ED nurses employed by a NZ district health board (DHB). The research questions were, firstly, “What are the perceptions of ED nurses in relation to retention?” and, secondly, “What are the success factors contributing to retention?” Qualitative interpretive description (ID) methodology was employed. The participants included 13 ED nurses who were purposively sampled and interviewed. The findings were thematically analysed using Braun and Clarke’s (2022) approach. The demographic characteristics of participants were: 1 male nurse, 12 female nurses; 1 nurse who identified as Māori, 1 Asian nurse and 11 European nurses. The average age was 35 years, and nursing experience ranged from 18 months to 40 years. Six themes were constructed. Theme one, personal satisfaction from being an ED nurse, captured reasons for taking the role. Theme two, using ways of coping, captured positive ways nurses coped in the ED. The third theme, workplace tensions, captured nurses’ experiences, struggles, and challenges while working in ED. Theme four, professional development is important, captured the importance of training and education for all ED nurses. Theme five, “we all chip in,” captured supportive relationships between team members in ED. Theme six, dissatisfaction with organisational structures, processes, and systems centred on the negative effect of existing systems, processes and structures within the organisation. The study concluded that pull (positive) and push (negative) factors operated simultaneously to inform personal, professional, interpersonal, and organisational factors that led to retention decisions. Key recommendations for nursing practice include consistently valuing and acknowledging ED nurses through positive organisational cultures, healthy workplaces, incentives, regular professional development, and career progression. Furthermore, improved infrastructures, processes and systems to protect staff from violence and aggression is recommended. In addition, support for both senior ED and early career nurses is needed. In terms of nursing education, it is imperative to provide courses on stress, coping, teamwork, communication and leadership. Future research using mixed methods research approaches with large population samples across several hospitals is recommended.